Green Banking and Sustainable Finance: An Analysis of Islamic Banking Customer Perception in Indonesia - Marifatul Hikmah; Henny Mulyati; Muhamad Zulkifli; Gusneli (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
The goal of this research is to investigate how consumer perception affects Indonesian Islamic banks provide sustainable finance support in the framework of green banking. Using Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS, A quantitative approach was employed. Questionnaires were used to gather information from Indonesian Islamic bank clients. Each construct met the necessary standards for validity and reliability, according to the model of measurement evaluation. The Fornell-Larcker criterion and an HTMT ratio of 0.858 (< 0.90) were used to establish discriminant validity. The suggested hypothesis is backed by the findings of hypothesis testing, which showed that customer perception significantly improves sustainable finance support. These results imply that fostering a favorable customer perception is a crucial tactic in encouraging Islamic banks to adopt sustainable financial products. This research adds to our understanding of green banking within the framework of Indonesian Islamic banking and gives important guidance for bank management and financial regulators to push a sustainable finance agenda based on Shariah values